Gangguan Jaringan Sistem Online Departemen Perhubungan dalam Proses Penyijilan Awak Kapal oleh PT. Menara Suar Maritim Cabang Tanjung Balai Karimun - Sebtiel Rikardo Marpaung; Syarifur Ridho; Eka Fransiska (Port Management and Maritime Administration Journal, 2026)
This study aims to determine the extent of the influence of network disruptions within the Ministry of Transportation's online system on the crew signing process (sign-on/sign-off) conducted by PT. Menara Suar Maritim, Tanjung Balai Karimun Branch. The online system is a vital instrument that supports the administrative efficiency of crew signing, serving as legal evidence and fulfillment of employment requirements on board in accordance with shipping regulations in Indonesia. In practice, this system acts as a link between shipping companies, government agencies, and the crew; thus, network stability is a decisive factor for the success of the process. However, frequent network disruptions lead to service delays, accumulation of physical files, and hindered ship departure schedules, which impact company operations. The method used is field research through direct observation, interviews with relevant parties, and library research by reviewing relevant regulations and literature to strengthen the analysis. This research is expected to serve as a reference for shipping companies and related agencies in improving the effectiveness of crew signing services to support smooth operational processes while ensuring maritime safety. The results indicate that network disruptions directly affect the document verification stage, as well as the data input process for the issuance of signing certificates.